Geological and environmental implications of the utilisation of geothermal energy in the Lahendong working area, Indonesia - Mukti, Mentari; Tomaszewska, Barbara; Starczewska, Magdalena; Ningrum, Eva Oktavia (Geology, Geophysics and Environment, 2022)
This study presents the characteristics of the Lahendong geothermal working area (GWA) in terms of the geological, geophysical, geochemical, and environmental implications. The investigated area is located in the Sulawesi North Arm, where the volcanic arc extends from Sangihe Island to Minahasa with two major strike-slip faults. NE–SW (northeast-southwest) trending faults control the thermal surface manifestation. The geothermal field is grouped into two hydrochemical systems: acid-sulphate-chloride (acid reservoir) and chloride (closer to neutral) types. The environmental implication analysis shows that the North Sulawesi province is experiencing water shortages due to excessive mining activities, inadequate wastewater management, and periods of drought. Although geothermal wastewater is being re-injected, the possibility of water contamination by hazardous materials from geothermal power plant activity is still evident. This study reviews the actual geothermal utilisation in the form of the 120 MWe power plant, the 500 kWe binary power plant, while the heat from geothermal energy is used for palm sugar production. Furthermore, the article also analyses the potential of the rational use of geothermal resources in this area. As a result of the high salinity and silica concentration of the brine, the geothermal wastewater should be treated before further utilisation and it potentially benefits both local communities and geothermal companies.